2020
DOI: 10.1155/2020/1845969
|View full text |Cite
|
Sign up to set email alerts
|

The Peroxisome Proliferator-Activated Receptor γ Agonist Pioglitazone Protects Vascular Endothelial Function in Hypercholesterolemic Rats by Inhibiting Myeloperoxidase

Abstract: Objective. Hypercholesterolemia-(HC-) induced endothelial dysfunction is the first step of atherogenesis, and the peroxisome proliferator-activated receptor c (PPARc) has been reported to attenuate atherosclerosis formation; however, the underlying mechanisms are not fully understood. e present study was designed to determine whether myeloperoxidase (MPO) mediates HC-induced endothelial dysfunction and the role of the PPARc agonist pioglitazone (PIO) in attenuating endothelial dysfunction. Methods. Male Wistar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Vascular relaxation induced by acetylcholine is dependent on the presence of endothelial cells and vascular relaxation induced by sodium nitroprusside is endothelium-independent [ 25 ]. Zhang et al showed that endothelium-dependent relaxation to acetylcholine is impaired by hypercholesterolemia but not endothelium-independent relaxation to sodium nitroprusside [ 26 ]. Our study indicated the consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular relaxation induced by acetylcholine is dependent on the presence of endothelial cells and vascular relaxation induced by sodium nitroprusside is endothelium-independent [ 25 ]. Zhang et al showed that endothelium-dependent relaxation to acetylcholine is impaired by hypercholesterolemia but not endothelium-independent relaxation to sodium nitroprusside [ 26 ]. Our study indicated the consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is the first step in the development of atheroma. Hypercholesterolemia is one of the most common causes of endothelial dysfunction that causes stenosis of the aorta of the heart (Zhang et al, 2020). Cholesterol is required for some physiological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction is the first stage that leads to atherogenesis. Hypercholesterolemia is known as one of the most frequent causes of endothelial dysfunction, inducing constriction of large blood vessels in the heart [ 4 ]. Cholesterol itself is needed for many physiological processes.…”
Section: Introductionmentioning
confidence: 99%